Fekunditas ikan gelodok, Boleophthalmus boddarti (Pallas 1770) di Pantai Brebes [Fecundity of Boddart's goggle-eyed goby, Boleophthalmus boddarti (Pallas 1770) in Brebes Coast] - Djumanto Djumanto; Eko Setyobudi; Rudiansyah Rudiansyah (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2012)
Boddart's goggle-eyed goby (Boleopthalmus boddarti) is often found in mudflats of estuary and coastal areas, has ability to walk on land and spawn inside the mud pits of hiding hole. The aim of this research was to study the fecundity and reproductive potential of mudskipper. Sampling was conducted in Losari, Tanjung and Bulakamba sub districts of Brebes regency from February to March 2012. Fish were caught using trap nets of 100 units for each station, then was repeated three times every two weeks. All fish samples were collected and preserved in 10% formaldehyde, then transported to the laboratory for measurement of length, weight, gonad weight, and counting the number and diameter of eggs. The results showed that the smallest size of brood stock was 15.0 cm in length and 30 g in weight. The ratio of male and female showed a balance of 1:1. Fish condition factor tended to decrease when the levels of gonadal maturity increase. The gonad maturity index of the spawned brood stock ranged from 0.8 to 7.9%. The fecundity for each female brood stock ranged from 4,874 to 28,028 eggs with a mean of 14,520 eggs. Relative fecundity ranged from 108 to 577 with a mean of 303 eggs/g body weight. Gonad of mature female consisted of one size group, and egg diameter ranged from 0.38 to 0.55 mm with a mean of 0.47 mm. AbstrakIkan gelodok (Boleopthalmus boddarti) merupakan jenis ikan yang banyak dijumpai di daerah muara dan pantai berlumpur, ikan yang mampu berjalan di darat dan memijah di dalam lubang lumpur tempat persembunyian. Tujuan pe-nelitian adalah untuk menentukan fekunditas ikan gelodok dan mengkaji potensi reproduksinya. Penangkapan ikan di-lakukan di Kecamatan Losari, Tanjung dan Bulakamba, Kabupaten Brebes di antara bulan Februari dan Maret 2012. Penangkapan ikan menggunakan jaring perangkap sebanyak 100 unit tiap stasiun, kemudian diulang sebanyak tiga kali dengan jarak antarwaktu sampling dua minggu. Semua ikan yang terperangkap dikumpulkan kemudian diawetkan dalam formalin 10% dan dibawa ke laboratorium untuk dilakukan pengukuran panjang total dan bobot tubuh, bobot gonad, penghitungan jumlah serta diameter telur. Hasil pengamatan menunjukkan ukuran ikan gelodok matang gonad ter-kecil adalah 15,0 cm dan bobot 30 g. Nisbah kelamin jantan dan betina menunjukkan jumlah yang seimbang 1:1. Faktor kondisi ikan cenderung menurun seiring meningkatnya tingkat kematangan gonad. Indek kematangan gonad pada induk siap pijah berkisar 0,8-7,9%. Fekunditas telur dalam gonad berkisar 4.874-28.028 dengan rerata 14.520 butir. Fekunditas relatif berkisar 108-577 dengan rerata 303 butir butir/g berat induk. Pada induk matang gonad terdapat satu kelom-pok ukuran, dan diameter telur berkisar 0,38-0,55 mm dengan rerata 0,47 mm.